Web Assessment of Sisfo Faculty of Science & Technology, Universitas Buddhi Dharma Tangerang Using The Likert Scale Method - Muhammad Subhana; Indra Wijaya (Komunitas Dosen Indonesia, 2022)
Technological developments make it easy to send and receive information that is accessed from various kinds of hardware and is supported by software in the design of the information system itself. tertiary institutions have 3 roles in carrying out teaching and learning activities from students, lecturers, to employees in the implementation of teaching, therefore information from various data is needed for processing information used in teaching and learning, information processing includes many administrative activities from student data, lecturers, employees, and others in lectures, mid-semester exams and Semester Final Exams and many others in accordance with the circumstances regarding existing activities, and a web-based information system design has been made for students and lecturers, employees in carrying outdaily activities in lectures at the university, in this study assessing the web that supports all administrative activities at the Faculty itself takes respondents of 18 students as a sample, using the Likert scale method on counting and voting from them in answering 6 questions, the average score on the web assessment itself is very good in each filled out questionnaire questions.